Musealization at Brazilian memory spots (Cadernos de Sociomuseologia, 2023)
This article presents a synthesis of musealization processes for the creation of memory points - institutions for the rescue of community memory and fostered by a homonymous brazlian public policy in the field of culture. Through a bibliographic review and content analysis of documentary sources, what is musealized in these institutions are analyzed, including the narrative conflicts involved in the constitution of those points and their relationship with the communities present in their territories. It is concluded that the musealization processes involved in the creation of memory points involve rescuing community ties around their struggles and daily tasks, with the use of participatory methodologies, such as sensitization and qualification actions with community members around the themes of memory and right to memory; and participatory inventories. In addition to the actors and community groups involved in the creation of the points, other external actors - such as universities and IBRAM [Brazilian Institute of Museums] - can both act as catalysts and supporters of community actions, especially in training and qualification processes, as well as sources of tension and disturbance of collective participatory logic.Keywords: Memory points; social museology; methodology.